Understanding Aphthous Ulcers: Causes, Symptoms, and Management (Academia Journal of Medicine, 2023)
Aphthous ulcers, also known as canker sores, are a  common and painful condition affecting the oral  mucosa. This review article aims to provide an in depth understanding of aphthous ulcers, including  their causes, symptoms, and management. The article  examines the different types of aphthous ulcers, their  epidemiology, etiology, clinical presentation, and  current treatment options.
Keywords: Aphthous ulcer; Cause; Management